ANALISIS MOTIVASI BELAJAR SISWA KELAS VA PADA PEMBELAJARAN DARING DI SD NEGERI 027 SAMARINDA ULU - Euis Kusumarini; Margareta Nona Vinta (BADAN PENERBIT STIEPARI PRESS, 2021)
This research is motivated by the existence of an online learning process that requires learning to be carried out using theapplication, WhatsApp both providing material and collecting assignments. This study aims to analyze the learning motivation of class VA students in online learning at SD Negeri 027 North Samarinda. The technique of determining the subject used in this study is snowball sampling and data collection techniques with interviews and documentation. The data analysis technique used was data collection, data presentation, and conclusion drawing. The type of triangulation used is source triangulation. The results of the research on the learning motivation of class VA students in online learning at SD Negeri 027 Samarinda Ulu, that students' learning motivation in online learning can be seen through the classification of indicators, including the desire and desire to succeed, the encouragement and learning needs, the existence of hopes and aspirations for the future, the existence of appreciation in learning, the existence of interesting activities in learning and the existence of a conducive learning environment. The obstacle in online learning is that learning is not interesting because it is only through theapplication WhatsApp and the material provided by the teacher is only a video from YouTube and the explanation from the teacher is lacking so it is difficult to understand the material provided. Students are less happy with online learning and prefer face-to-face learning. Because online learning is always a lot of work to do and can't meet other friends.